The effect of co-administration of vitamin E and C supplements on plasma oxidative stress biomarkers and antioxidant capacity: a GRADE-assessed systematic review and meta-analysis of randomized controlled trials with meta-regression - Moabedi, Mahdi; Milajerdi, Alireza (Frontiers in Immunology, 2025)
BackgroundThere is no conclusion on the effect of vitamins E and C on plasma biomarkers of oxidative stress and antioxidant status. We conducted this meta-analysis to gain a clearer view of this area.MethodsWe performed a systematic search in online databases using the relevant keyword combination. Randomized controlled trials that investigated the effect of vitamins E and C simultaneously, compared with control, on oxidative stress and antioxidant status biomarkers were included in the analyses.ResultsA total of 17 trials were included in the meta-analysis, building a total sample size of 965. The dosage of vitamin E and C supplements varied from 54 to 536 and 250 to 1000 mg/d, respectively, across included studies. We found significant results for MDA [WMD: -0.38, 95% CI: -0.48, -0.28 µg/L, P <0.001], LP [WMD: -1.01, 95% CI: -1.49, -0.54 µg/L, P <0.001], TAC [WMD: 0.09, 95% CI: 0.05, 0.13 mmol/L, P <0.001], and GPx [WMD: 1251.74, 95% CI: 258.92, 2244.56 U/L, P = 0.013], but not for SOD [WMD: 16.69, 95% CI: -29.40, 62.78 U/L, P = 0.278]. Regarding subgroup analysis, only studies on unhealthy participants showed a significant effect on MDA [WMD: -1.62, 95% CI: -2.08, -1.15 µg/L, P <0.001] and TAC [WMD: 0.08, 95% CI: 0.03, 0.14 mmol/L, P <0.001], unlike LP, where significance was only observed in healthy adults [WMD: -0.41, 95% CI: -0.45, -0.37 µg/L, P <0.001]. Moreover, only studies in which a placebo was administered, supplementation of vitamins showed significant effects on MDA [WMD: -0.47, 95% CI: -0.58, -0.35 µg/L, P <0.001], LP [WMD: -1.28, 95% CI: -1.85, -0.72 µg/L, P <0.001], and TAC [WMD: 0.10, 95% CI: 0.05, 0.15 mmol/L, P <0.001].ConclusionOur review and analyses revealed that a combination of vitamin C and E has a beneficial effect on oxidative stress biomarkers and antioxidant status.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024590197, identifier CRD42024590197.